Peranan Etika Bisnis Dalam Industri Kopi: Studi Kasus PT. Kapal Api Dan PT. Nestlé Indonesia - Jecky Danvelty Rumaropen; Stivano Theofilli kolamban; Dion Tumbelaka; Meidian Sanggale; Jelin Bayak; Wini witarin; Jonathan gabrisch; Grace Christien Sumakul (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the implementation of business ethics at PT Kapal Api and Nestlé and its impact on corporate sustainability. Business ethics play a crucial role in maintaining reputation, building consumer trust, and fostering harmonious relationships with stakeholders. PT Kapal Api and Nestlé face various challenges in applying ethical principles, particularly in aspects of transparency, social responsibility, and regulatory compliance. The study finds that companies that uphold strong business ethics tend to have higher consumer loyalty and stronger relationships within their business environment. Conversely, ethical misconduct can negatively impact a company’s image and decrease public trust. Therefore, a strong commitment to business ethics must be continuously reinforced to maintain competitiveness and ensure corporate sustainability amid increasingly intense industry competition.